Comparison of knowledge about smoking and passive smoking and urinary cotinine levels in pregnant women and their partners in Mongolia: A cross-sectional study - Naoko Hikita; Megumi Haruna; Masayo Matsuzaki; Emi Sasagawa; Minoru Murata; Ariunaa Yura; Otgontogoo Oidovsuren (JMIR Publications, 2019)
This study aimed to compare knowledge about smoking, including passive smoking, and urinary cotinine (UC) levels in pregnant women and their partners in Mongolia. The study was conducted between November 2015 and January 2016 in Darkhan-Uul Province, Mongolia. Pregnant women with less than 20 weeks' gestation were recruited, and their partners were also invited to participate. Self-administered questionnaires and urine samples were used to collect data. Knowledge about smoking including passive smoking was measured using 14 questions. Data were analyzed using a Student's t-test, a chi-squared test, a one-way analysis of variance, and the Tukey-Kramer method for post-hoc analysis. Correlations were measured by computing Pearson's r or Spearman's ρ. A total of 508 pregnant women and 227 partners participated in this study; of these, 221 couples' data were analyzed. Pregnant women's scores on knowledge about smoking and passive smoking were significantly higher than those of their partners (9.4 ± 2.9 and 8.7 ± 3.1, respectively; p = 0.017). Pregnant women's and their partners' scores were slightly correlated (r = 0.163, p = 0.015). Pregnant women's and their partners' UC levels were significantly correlated (ρ = 0.250, p < 0.001). This study is the first to examine knowledge about smoking and passive smoking and UC levels among pregnant women and their partners in Mongolia. Because pregnant women's and their partners' scores and UC levels were positively correlated, health education on the harm caused by smoking and passive smoking should be provided to both pregnant women and their partners.